The impact of a training program in sustainable development practices on developing awareness of the environmental problems and volunteer work skills of Sattam University female students - Al-Najjar, Fatima Kamal Ahmed Ali (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the effectiveness of a training program in sustainable development practices based on problem solving for the development of environmental awareness and volunteer work skills of students of the Faculty of Science and Humanities at the University of Sattam Bin Abdul Aziz. The study used the semi-experimental method. The researcher used two tools (environmental awareness scale, attitude test). The study sample consisted of (45) female students of scientific departments at the University of Sattam Bin Abdul Aziz in Aflaj and Aldalm governorates. The results showed the effectiveness of the training program in developing the environmental awareness and volunteer work skills of the students of the study group. The value of "T" on the scale of awareness of total environmental problems (8.325), which is a statistical value at the level of significance (α = 0.01), and the value of "T" in the test of attitudes to the skills of volunteer work (24.7) α = 0.01). The results revealed a statistically significant relationship between awareness of environmental problems and volunteer work skills (0.81). In light of the results, a number of recommendations and proposals were presented to increase environmental awareness and volunteer work skills among Saudi youth.